Road to resilience: a systematic review and meta-analysis of resilience training programmes and interventions - Joyce, Sadhbh; Shand, Fiona; Tighe, Joseph; Laurent, Steven J; Bryant, Richard A; Harvey, Samuel B (BMJ open, 2018)
ObjectivesTo synthesise the available evidence on interventions designed to improve individual resilience.DesignA systematic review and meta-analysisMethodsThe following electronic databases were searched: Ovid Medline, Ovid EMBASE, PsycINFO, Ovid Cochrane and WHO Clinical Trials Registry in order to identify any controlled trials or randomised controlled trials (RCTs) examining the efficacy of interventions aimed at improving psychological resilience. Pooled effects sizes were calculated using the random-effects model of meta-analysis.Outcome measuresValid and reliable measures of psychological resilience.ResultsOverall, 437 citations were retrieved and 111 peer-reviewed articles were examined in full. Seventeen studies met the inclusion criteria and were subject to a quality assessment, with 11 RCTs being included in the final meta-analysis. Programmes were stratified into one of three categories (1) cognitive behavioural therapy (CBT)-based interventions, (2) mindfulness-based interventions or (3) mixed Interventions, those combining CBT and Mindfulness training. A meta-analysis found a moderate positive effect of resilience interventions (0.44 (95% CI 0.23 to 0.64) with subgroup analysis suggesting CBT-based, mindfulness and mixed interventions were effective.ConclusionsResilience interventions based on a combination of CBT and mindfulness techniques appear to have a positive impact on individual resilience.